First record from Peru of Raillietina (R.) demerariensis (Cestoda: Taenioidea) in Rattus rattus norvegicus. - Martínez, Rosa (1998)
It is registered by first time in Perú, the occurrence of Raillietina (R.) demerariensis (Daniels, 1895) in Rattus rattus norvegicus from the district of San Martin de Porres in the department of Lima.